Electron beam treatment for the removal of 1,4-dioxane in water and wastewater - Pearce, Robert (Water science and technology : a journal of the International Association on Water Pollution Research, 2023)
Electron beam (e-beam) treatment uses accelerated electrons to form oxidizing and reducing radicals when applied to water without the use of external chemicals. In this study, electron beam treatment was used to degrade 1,4-dioxane in several water matrices. Removal improved in the progressively cleaner water matrices and removals as high as 94% to 99% were observed at a dose of 2.3 kGy in secondary effluent. 1,4-dioxane removal was confirmed to be primarily through hydroxyl radical oxidation. The calculated electrical energy per order was found to be 0.53, 0.26, and 0.08 kWh/m3/order for secondary effluent (Avg. total organic carbon (TOC) 9.25 mg/L), granular activated carbon effluent (TOC 3.46 mg/L), and ultrapure water, respectively, with a 70% generation and transfer efficiency applied